ANALYSIS OF HIGH ORDER THINKING SKILLS IN PHYSICS IN 21ST CENTURY LEARNING - riswanto, riswanto; Rosa, Friska Octavia; Lestari, Puji; Febriana, Fani; Fatmawati, Eka Lia (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The purpose of this research is to analyze the extent to which High Order Thingking Skill is applied in physics learning at MA Muhammadiyah Boarding School Metro and analyze students' HOTS ability in the current 21st century learning. In this article, the type of research used is qualitative research. The data collection stage consists of 3 stages, namely observation and interview, literature study, and data analysis stage. The data analysis technique uses data triangulation techniques by comparing 3 data sources. The results showed that physics learning at MA Muhammadiyah Boarding School Metro has been integrated with High Order Thinking Skill. This is evidenced by the use of the PjBL method. The PjBL method allows students to use reasoning to create a project. However, the application of HOTS in physics learning has not been fully successful because there are still students who have difficulty in applying formulas and working on problems. In 21st century learning, teachers are expected to continue to improve their abilities and innovate in the application of methods, strategies, and learning media that can support students' HOTS.